Instrumento de evaluación de la percepción de los contrastes mínimos en lengua de señas – adaptación a la lengua de señas chilena - Herrera, Carlos González (2022)
The perception of the minimum contrasts in sign language corresponds to the identification of the pairs of minimum contrast in visuogestural modality. Its importance lies in the contribution it can make to knowledge of language development in sign language mode. Objective: To adapt and search for evidence of validity and reliability of an instrument for evaluating the perception of minimal contrasts in Chilean Sign Language (LSCh). Method: The development of the instrument was based on a test to assess the perception of minimal contrasts in Brazilian sign language, which measures the domain of minimal contrast pairs in visuogestural modality. Therefore, the content adaptation and validation process occurred in 7 methodological stages. First, a survey of the pairs of minimum contrast in LSCh (Stage 1) was performed by the author of the test. In Stage 2, the analysis of expert judges (four fluent adults in the LSCh) was carried out, who evaluated the degree of adequacy, vocabulary and representativeness of the words selected in Stage 1. Afterwards (Stage 3), the pairs of minimal contrast and were analyzed by 6 nonspecialist judges (Deaf children and adolescents) (Stage 4). In Stage 5, the test was prepared and elaborated. In stage 6 the selected pairs of words were recorded on video with the test instructions. The video was made by an LSCh interpreter. In stage 7, a pilot study was carried out with the participation of 6 deaf children and adolescents. Subsequently, evidence of reliability was sought, 10 children and adolescents aged between 7 and 14 years participated, who were subjected to test-retest and inter-rater reliability. Results: In Stage 1, 69 pairs of minimal contrast were lifted in LSCh. In Stage 2, the judges evaluated the degree of adequacy by selecting 44 pairs of minimum contrast; later they evaluated vocabulary, selecting 29 pairs and; representativeness, selecting 24 final pairs. In Stage 3, the 24 selected pairs were designed. In Stage 4, non-specialist judges evaluated and redesigned 6 pairs of minimal contrast. In Stage 5, the test was prepared and elaborated. In Stage 6, the video was recorded with the instructions in LSCh. Finally, in Stage 7, in the pilot study, all the children managed to perform all the items, so the stimuli contained in the test contemplated the objective of the evaluation. In the test-retest reliability, a strong association is observed between the results of the test and those of the retest (Rho=0.741; p= 0.014). In the inter-rater reliability, it is observed that the concordance values obtained vary between 0.77 to 1 (p0.001), indicating concordance varying from good to perfect. Conclusions: The Instrument for the Evaluation of the Perception of Minimum Contrasts in Chilean Sign Language is made up of 24 pairs of minimum contrast and presents content validity and satisfactory reliability for its use in the Chilean population.